SISTEM POLITIK DAN PEMERINTAHAN INDONESIA SETELAH REFORMASI - PURWOKO, PURWOKO (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractSince it Independence, Indonesiaâ€™s political and governmental system had been changingseveral times. It was in terms of searching political forms that accordingly to Indonesian conditionsand to realized stable, democratic government, and created prosperous society. In â€œOld Orderâ€ (1945-1959),there was democratic political and governmental system but in the same time economicdevelopment and prosperity of society were ignored. After the coup dâ€™etat attempt in October 1st 1965,in which military took power, they directed political and governmental system to realized economicdevelopment and prosperity. In that time shaped stable political and government sytem but it was notdemocratic and arised an abuse of power. The past experiences that extremely both, messy in oneside and quite in other side tried to be reconstruct by mixed presidential and parliamentary system. Infact that experiment created devided government and cohabitation. It was conscious that thereconstruction of political infrastructure such as society and political party was the key of political andgovernmental development.Keywords : Political and governmental system, democracy, economic development, mixedpresidential and parliamentary system